Mitochondrial genome and phylogenetic position of the sliteye shark Loxodon macrorhinus. (1st November 2016) - Wang, Junjie; Chen, Hao; Lin, Lingling; Ai, Weiming; Chen, Xiao
Abstract: The sliteye shark Loxodon macrorhinus is the only member of the genus Loxodon in the family Carcharhinidae. In this study, we first present the complete mitochondrial genome of L. macrorhinus and determine its phylogenetic position within Carcharhinidae based on relative mitogenomes. The mitochondrial genome was 16 702 bp in length with the typical gene order in vertebrates. The overall base composition of the H-strand was 31.7% A, 25.8% C, 13.1% G, and 29.4% T. Two start codons (ATG and GTG) and three stop codons (TAG, AGG, and TAA/T) were found in the protein-coding genes. The tRNA genes ranged from 67 bp to 75 bp. Loxodon macrorhinus was placed as sister to the genus Scoliodon in the Bayesian tree.